Insights into CO2 methanation mechanism on cubic ZrO2 supported Ni catalyst via a combination of experiments and DFT calculations. (1st January 2021) - Xu, Xianglan; Tong, Yunyan; Huang, Jin; Zhu, Jia; Fang, Xiuzhong; Xu, Junwei; Wang, Xiang
Graphical abstract: Highlights: CO2 methanation follows the formate pathway on Ni/c-ZrO2 . The CO2 * adsorbed states on the Ni/ZrO2 interface are hydrogenated to CH4 . The CO2 * adsorbed states at Ni sites convert CO without further conversion to CH4 . ZrO2 improves Ni reducibility, and promotes H2 O formation via H-spillover effect. Y 3+ doping stabilizes cubic ZrO2 support and improves the Ni/ZrO2 catalyst. Abstract: The CO2 methanation mechanism was studied via combined in-situ FTIR and DFT calculations on the cubic ZrO2 supported Ni catalyst. The formation and evolution of CO2 initial adsorbed species were addressed. The bicarbonates produced from CO2 reacting with surface OH sites are transformed to the CO2 * adsorbed state on the Ni/ZrO2 interface (CO2 *-interface) that are hydrogenated to CH4 . The CO2 adsorbed states (CO2 *-Ni) generated from CO2 reacting with surface Ni sites are hydrogenated to CO* as a byproduct rather than an intermediate for methanation. The formate pathway is dominated for methanation on Ni/ZrO2, in which bidentate formates hydrogenation to H2 COO* is the rate-determining step with the activation energy of 1.01 eV. The presence of ZrO2 support improves the electron mobility and reducibility of Ni, and induces H-spillover effect to promote H2 O* formation. Y 3+ doping into the support of Ni/ZrO2 stabilizes the c-ZrO2 phase and promote methanation activity of the catalyst.